Aging and the cancer burden in Latin America and the Caribbean: Time to act. Issue 5 (September 2019) - Pilleron, Sophie; Soerjomataram, Isabelle; Soto-Perez-de-Celis, Enrique; Ferlay, Jacques; Vega, Enrique; Bray, Freddie; Piñeros, Marion
Abstract: Objective: To describe the cancer burden in adults aged 65 years and older in Latin America and the Caribbean to serve as rational for improving cancer control planning among region's older population. Materials and Methods: Using the up-to-date GLOBOCAN estimates for 2018, we describe the cancer burden including key patterns for the major cancer sites among adults aged 65 years and older in Latin America and the Caribbean. We also predict the future burden in 2040 by applying population projections, assuming no changes in incidence rates over time. Results: In 2018, an estimated 679, 000 new cancer cases occurred among older adults in LAC, representing almost half (48%) of the total incidence burden (43% in Central America, 49% in South America, and 52% in the Caribbean). Prostate, colorectum, and lung were the most common cancers among older males in South America and the Caribbean, with non-melanoma skin cancer ranking third in Central America. Among older females, the most common sites were breast, colorectum, and non-melanoma skin cancer, except in the Caribbean, where lung cancer ranked third. Overall, the number of new cancer cases among older adults in the region is expected to double by 2040, reaching 1.6 million new cases. Conclusion: Our findings highlight the need for an urgent adaptation of healthcare systems across LAC by improving training in geriatrics for the oncology workforce, and by including older adults in clinical guidelines, insurance schemes, and cancer prevention policies.